Underreported coal in statistics: A survey-based solid fuel consumption and emission inventory for the rural residential sector in China. (1st February 2019) - Peng, Liqun; Zhang, Qiang; Yao, Zhiliang; Mauzerall, Denise L.; Kang, Sicong; Du, Zhenyu; Zheng, Yixuan; Xue, Tao; He, Kebin
Highlights: Solid fuel consumption rises with the increase in Heating Degree Days. A transition from biofuel to coal occurs with per capita income growth. Estimated coal consumption is 62% higher than that reported in official statistics. An improved emission inventory of the residential sector is built in China. Our work provides a new approach of obtaining data for other developing countries. Abstract: Solid fuel consumption and associated emissions from residential use are highly uncertain due to a lack of reliable statistics. In this study, we estimate solid fuel consumption and emissions from the rural residential sector in China by using data collected from a new nationwide field survey. We conducted a field survey in 2010 which covered ∼17, 000 rural residential households in 183 counties in China, to obtain data for solid fuel consumption and use patterns. We then developed a Generalized Additive Model (GAM) to establish the relationship between solid fuel consumption and heating degree days (HDD), income, coal production, coal price, and vegetation coverage, respectively. The GAM was used to estimate solid fuel consumption in rural households in China at the county level. We estimated that, in 2010, 179.8Tg of coal were consumed in Chinese rural households for heating and cooking, which is 62% higher than that reported in official energy statistics. We found that large quantities of rural residential coal consumption in the North China Plain were underreported in energy statistics. For instance, estimated coal consumption in rural households in Hebei (one of most polluted provinces in China) was 20.8Tg in 2010, which is twice as high as government statistics indicate. In contrast, modeled national total consumption of crop residues (used as fuels) we found to be ∼50% lower than reported data. Combining the underlying data from the survey, the GAM and emission factors from literature, we estimate emissions from China's rural residential sector in 2010 to be: 3.3Tg PM2.5, 0.6Tg BC, 1.2Tg OC, 2.1Tg VOC, 2.3Tg SO2, 0.4Tg NOx, 43.6Tg CO and 727.2Tg CO2, contributing to 29%, 35%, 38% and 26% of national total PM2.5, BC, OC, and CO emissions respectively. This work reveals that current emission inventories in China likely underestimate emissions from coal combustion in rural residential households due to missing coal consumption in official statistics, especially for the heavily polluted North China Plain (NCP) region. Per capita income appears to be the driving factor that results in the difference between surveyed data and official data. Residents with high income prefer commercial energy and have a higher per capita fuel consumption than lower income residents. Therefore, rural residential coal combustion may contribute even more to regional air pollution than the large contributions previously identified.